Pengetahuan dan Sikap Ibu Post Partum dalam Perawatan Organ Reproduksi Pasca Persalinan Masa Pandemi COVID-19 - Herawati Jaya; Intan Kumalasari (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
The corona virus has spread in various parts of the world, not only countries, provinces or districts, but even in remote villages this virus has caused an alarming impact. Knowledge and attitudes of mothers during the post partum period are very important in order to avoid infection which results in long recovery from reproductive organs. During the postpartum period, a mother is very susceptible to infection. Infection as another important factor causing maternal death often occurs due to poor hygiene after childbirth that is not treated. Therefore, the cleanliness of the reproductive organs is very important to prevent infection. The purpose of this study was to describe the knowledge and attitudes of postpartum mothers in caring for reproductive organs after childbirth during the COVID-19 pandemic. this research method is descriptive. The sampling technique used purposive sampling, the subjects of this study were 96 respondents. This research was conducted in July 2021. The results showed that of 96 respondents the knowledge about caring for reproductive organs during the pandemic was still not good, namely 71.76% (less than 76%) and for attitudes, it was found that respondents had positive behavior as much as 68.26%. The conclusion is the better the knowledge possessed by the mother about the treatment of reproductive organs, the better the action for disease prevention will be. Vice versa. So with good knowledge, it is hoped that preventive measures will be even better.